2002
DOI: 10.1007/s00330-002-1462-7
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injuries: imaging of abdominal and pelvic injuries

Abstract: The availability of new imaging modalities has altered the diagnostic approach to patients with abdominal and pelvic trauma. Computed tomography and ultrasound have largely replaced diagnostic peritoneal lavage. Ultrasound is used in most trauma centers as the initial imaging technique for the detection of hemoperitoneum and helps to determine the need for emergency laparotomy. Computed tomography allows for an accurate diagnosis of a wide range of traumatic abdominal and pelvic conditions. The speed of single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 40 publications
1
28
0
5
Order By: Relevance
“…Abandonment of conventional radiographs may reduce the total effective dose by 24.7% as compared to the use of both imaging techniques in combination [3]. Our results further show that thin-slice technique can increase diagnostic accuracy up to 100% and that by use of common thoraco-abdominal CT protocols [2,11], this information can be gained without any additional scanning. A highly interesting approach in this direction has just recently been proposed by Ptak et al, who showed that by the choice of a singlepass continuous whole-body CT protocol, total dose reductions of up to 17% were feasible [23].…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Abandonment of conventional radiographs may reduce the total effective dose by 24.7% as compared to the use of both imaging techniques in combination [3]. Our results further show that thin-slice technique can increase diagnostic accuracy up to 100% and that by use of common thoraco-abdominal CT protocols [2,11], this information can be gained without any additional scanning. A highly interesting approach in this direction has just recently been proposed by Ptak et al, who showed that by the choice of a singlepass continuous whole-body CT protocol, total dose reductions of up to 17% were feasible [23].…”
Section: Discussionsupporting
confidence: 44%
“…The significant advantage of computed tomography over conventional radiography previously has been demonstrated by others [3,[8][9][10][11][12][13]. With regard to MDCT, surprisingly high sensitivities for unstable thoraco-lumbar fractures, but rather low sensitivities for thoraco-lumbar fractures in general were observed by Wintermark et al [14].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Parenchymdiagnostik (dafür sind dünne Schichten primär nicht erforderlich) auf den Nachweis von Traumafolgen am Skelett und am Gefäßsystem ankommt und wenn multiplanare und dreidimensionale Darstellungen gefordert werden. [15,26].…”
Section: Ct-untersuchungstechnikunclassified
“…Breath holding may not be possible in trauma CT, and the speed of MDCT scanning further reduces breathing artefact 6,7 .…”
Section: Introductionmentioning
confidence: 99%